2020
DOI: 10.1016/j.disamonth.2020.101057
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Extrapulmonary illness - The Impact of COVID-19 on Nephrology care

Abstract: Coronavirus disease-2019 (COVID-19) has caused a pandemic that has affected millions of people worldwide. COVID-19 is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and is spread by close contact and by respiratory droplets. It has also impacted different aspects of caring for people with kidney disease, including those with acute kidney injury (AKI), chronic kidney disease (CKD), those requiring kidney replacement therapy (KRT), and those with a kidney transplant. All of these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In our study we retrospectively evaluated BMI in 381 of a total of 946 patients which more than 45% of our patients were categorized as overweight this may be either due to demographic features of admitted patients or due to more susceptibility to COVID-19 in this group of people but it has been shown that overweight patients have 1.84-fold odds of developing severe COVID-19 compared with normal-weight patients (22). Among different studies various incidence rates of AKI are reported through the globe and in our study group the incidence of AKI was estimated as 45.9%, this was consistent with the global trend toward the increased rate of AKI in COVID-19 patients compared with early reports (23,24). We demonstrated that those with AKI, compared to the non-AKI group, had a significantly higher mean of age (62 versus 50.2 years, P < 0.001), and a higher proportion of females (34.9% versus 44.9%, P = 0.002); the first one is commonly due to impaired immune system in older patients and probably due to increased baseline inflammation with aging which also may be a contributing factor resulting in AKI (25).…”
Section: Discussionsupporting
confidence: 90%
“…In our study we retrospectively evaluated BMI in 381 of a total of 946 patients which more than 45% of our patients were categorized as overweight this may be either due to demographic features of admitted patients or due to more susceptibility to COVID-19 in this group of people but it has been shown that overweight patients have 1.84-fold odds of developing severe COVID-19 compared with normal-weight patients (22). Among different studies various incidence rates of AKI are reported through the globe and in our study group the incidence of AKI was estimated as 45.9%, this was consistent with the global trend toward the increased rate of AKI in COVID-19 patients compared with early reports (23,24). We demonstrated that those with AKI, compared to the non-AKI group, had a significantly higher mean of age (62 versus 50.2 years, P < 0.001), and a higher proportion of females (34.9% versus 44.9%, P = 0.002); the first one is commonly due to impaired immune system in older patients and probably due to increased baseline inflammation with aging which also may be a contributing factor resulting in AKI (25).…”
Section: Discussionsupporting
confidence: 90%
“…17,18 In high income countries, delays are reported in accessing urgent treatment for myocardial ischaemia 1924 and stroke care, 2529 and there are impacts predicted for other vulnerable groups. 30–33…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In high income countries, delays are reported in accessing urgent treatment for myocardial ischaemia [19][20][21][22][23][24] and stroke care, [25][26][27][28][29] and there are impacts predicted for other vulnerable groups. [30][31][32][33] Recent data detailed a 220% increase in residential aged care deaths during the pandemic in England and Wales, with 14,520 'additional' deaths, 3 (i.e. neither expected nor caused by COVID-19 infection).…”
Section: What This Study Adds?mentioning
confidence: 99%
“…Evaluating urinary biomarkers such as B2M may help to identify COVID-19 patients with active CRS who are likely to become critically ill [17]. Acute kidney injury is largely associated with hemodynamic instability [25]. B2M is freely filtered by the glomerulus and completely reabsorbed by proximal tubular cells.…”
Section: Discussionmentioning
confidence: 99%